The Constitutionality of Minister of Home Affairs Regulations: A Study of Minister of Home Affairs Regulation No. 4 of 2023 on Acting Governors, Acting Regents, and Acting Mayors: Konstitusionalitas Peraturan Menteri Dalam Negeri: Studi Terhadap Peraturan Menteri Dalam Negeri Nomor 4 Tahun 2023 Tentang Penjabat Gubernur, Penjabat Bupati, Dan Penjabat Wali Kota - Taufiqurrahman (Universitas Islam Indonesia, 2024)
This research focuses on implementing regulations on the appointment of acting regional heads. This focus is motivated by content material that is not in line with the constitutional mandate. This is evidenced by the improper format of the arrangement, not containing a firm prohibition for the TNI/Polri to be appointed as acting, and the lack of involvement of the DPRD as a representative of the people in appointing acting regional heads. Based on these problems, this study answers the research question, namely whether the implementing regulations for filling the acting regional head are in accordance with the constitutional mandate? This research method is juridical normative through the approach of constitutional court decisions, laws and regulations and case approaches. The study concluded that the content material governing the appointment of acting regional heads is far from the constitutional mandate. The government has ignored the legal considerations established by the Constitutional Court in the context of appointing acting regional heads.Keywords: Acting, Constitutional Mandate, and Implementing Regulations. AbstrakPenelitian ini berfokus pada peraturan pelaksana Menteri Dalam Negeri Nomor 4 tahun 2023 tentang Penjabat Gubernur, Penjabat Bupati, dan Penjabat Wali Kota Penelitian ini dilatarbelakangi dari materi muatan yang tidak sejalan dengan mandat konstitusional. Hal ini dibuktikan dengan format pengaturan yang tidak tepat, tidak memuat larangan tegas bagi TNI/Polri untuk ditunjuk sebagai penjabat, dan minimnya keterlibatan DPRD sebagai representasi rakyat dalam penunjukan penjabat kepala daerah. Berdasarkan persoalan tersebut, penelitian ini menjawab pertanyaan penelitian yakni apakah peraturan pelaksana pengisian penjabat kepala daerah telah sesuai dengan mandat konstitusional? Metode penelitian ini yuridis normatif melalui pendekatan peraturan perundang-undangan dan pendekatan kasus. Temuan dalam penelitian ini bahwa materi muatan yang mengatur penunjukan penjabat kepala daerah jauh dari amanat konstitusional. Pemerintah telah mengabaikan pertimbangan hukum yang dibangun oleh Mahkamah Konstitusi (MK) dalam rangka penunjukan penjabat kepala daerah. Adapun saran dalam penelitian ini pembentuk undang-undang untuk segera membentuk ragam klasifikasi tindaklanjut putusan MK. Kata Kunci: Mandat Konstitusional, Penjabat, dan Peraturan Pelaksana.